Cladonia lichens on extensive green roofs: evapotranspiration, substrate temperature, and albedo - Heim, Amy; Lundholm, Jeremy (F1000 research, 2013)
Green roofs are constructed ecosystems that provide ecosystem services in urban environments. Shallow substrate green roofs subject the vegetation layer to desiccation and other environmental extremes, so researchers have evaluated a variety of stress-tolerant vegetation types for green roof applications. Lichens can be found in most terrestrial habitats.  They are able to survive extremely harsh conditions, including frequent cycles of desiccation and rehydration, nutrient-poor soil, fluctuating temperatures, and high UV intensities. Extensive green roofs (substrate depth <20cm) exhibit these harsh conditions, making lichens possible candidates for incorporation into the vegetation layer on extensive green roofs.  In a modular green roof system, we tested the effect of Cladonia lichens on substrate temperature, water loss, and albedo compared to a substrate-only control. Overall, the Cladonia modules had significantly cooler substrate temperatures during the summer and significantly warmer temperatures during the fall.  Additionally, the Cladonia modules lost significantly less water than the substrate-only control. This implies that they may be able to benefit neighboring vascular plant species by reducing water loss and maintaining favorable substrate temperatures.